THE ROLE OF THE MARKETING FACTORS TO DEVELOP THE AGRITOURISM INDUSTRY IN DAMBULLA TOURISM AREA - Dilhani Ruwanthika Weerasinghe, K.P.W. (University of Jaffna, 2019)
This research is an investigation on the role of the marketing factors to develop the agritourism industry in Dambulla tourism area. Agritourism is the application of tourism activities to the agriculture industry. As it is significantly developing a concept, the agritourism industry needs effective marketing practices. A problem which arises in this industry is the usage of marketing practices are a lack in the agritourism industry when it considers in the Sri Lankan context. There has been less previous evidence for analyzing the marketing practices in the agritourism industry. The objective of this study is to identify the role of the marketing factors to develop the agritourism industry in Dambulla tourism area. According to the study, product characteristics, pricing strategy, promotion, geographical location, physical appearance, employment characteristics were identified as marketing phenomena to develop this industry. Structured questionnaires were distributed among the two hundred tourists by using purposive sampling around the Dambulla area. Results of the study revealed that product characteristics, pricing strategy, promotion, geographical location, physical appearance, employment characteristics significantly play a significant role to develop the agritourism industry in this tourism area.
Keywords: Agriculture; agritourism and marketing factor